Protein tyrosine nitration in higher plants grown under natural and stress conditions - Corpas, Francisco J.; Palma, José M.; del Río, Luis A.; Barroso, Juan B. (Frontiers in Plant Science, 2013)
Protein tyrosine nitration is a post-translational modification (PTM) mediated by reactive nitrogen species (RNS) that is linked to nitro-oxidative damages in plant cells. During the last decade, the identification of proteins undergoing this PTM under adverse environmental conditions has increased. However, there is also a basal endogenous nitration which seems to have a regulatory function. The technological advances in proteome analysis have allowed identifying these modified proteins and have shown that the number and identity of the nitrated proteins change among plant species, analysed organs and growing/culture conditions. In this work, the current knowledge of protein tyrosine nitration in higher plants under different situations is reviewed.